The Development of Students' Critical Thinking Skills in Solving Torque and Rigid Body Equilibrium Problems Through STEM Learning Using Infusion-Based Collaborative Problem Solving - Andriani, Riza; Hidayat, Arif; Supriana, Edi (FKIP - Universitas Riau, 2024)
This study investigated how students use critical thinking skills in solving problems in Torque and rigid body equilibrium before and after using STEM learning Infusion based- Collaborative Problem Solving model. Embedded Design Experimental Model was used. The research instrument was eight essay questions in torque and equilibrium of rigid objects that had been validated. Quantitative data were obtained from the pretest and post-test score, pretest and post-test data were analyzed using N-gain to determine the improvement of students' critical thinking skills. Qualitative data was obtained from students' answers in the pretest and post-test. Data were analyzed descriptively to compare students' critical thinking skills before and after the intervention. The average critical thinking skills of students increased from 7.61 (pretest) to 38.84 (post-test) with an N-gain of 0.34, the improvement is categorized as moderate. The findings indicate that critical thinking skills can be cultivated through physics lessons using STEM learning with Infusion-Based Collaborative Problem Solving. Following the intervention, students demonstrated systematic critical thinking in answering questions.